The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0179396
|View full text |Cite
|
Sign up to set email alerts
|

Going to sleep in the supine position is a modifiable risk factor for late pregnancy stillbirth; Findings from the New Zealand multicentre stillbirth case-control study

Abstract: ObjectiveOur objective was to test the primary hypothesis that maternal non-left, in particular supine going-to-sleep position, would be a risk factor for late stillbirth (≥28 weeks of gestation).MethodsA multicentre case-control study was conducted in seven New Zealand health regions, between February 2012 and December 2015.Cases (n = 164) were women with singleton pregnancies and late stillbirth, without congenital abnormality. Controls (n = 569) were women with on-going singleton pregnancies, randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 30 publications
(46 reference statements)
10
83
0
Order By: Relevance
“…In our study, a PT intervention was implemented in a population of healthy, third-trimester, pregnant women during sleep in a clinical sleep laboratory environment over two nights. This study extends the work of Stacey et al ,2 Gordon et al ,3 McCowan et al ,4 and Warland and Mitchell52 by finding that supine sleep position in late pregnancy can be reduced with PT.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, a PT intervention was implemented in a population of healthy, third-trimester, pregnant women during sleep in a clinical sleep laboratory environment over two nights. This study extends the work of Stacey et al ,2 Gordon et al ,3 McCowan et al ,4 and Warland and Mitchell52 by finding that supine sleep position in late pregnancy can be reduced with PT.…”
Section: Discussionsupporting
confidence: 86%
“…Women in our study preferentially settled to sleep on their left for 73% of the nights and right for 20% of the nights. This is corroborated by McCowan et al 4 who reported a significant increase in left-sided going-to-sleep position (43% to 58%) and small decrease in supine going-to-sleep position (5% to 3.8%) in New Zealand over an approximate 5-year period following publicity of The Auckland Stillbirth Study by Stacey et al 2. If the supine sleeper is to be identified by history taking and stratified for targeted education or intervention, obstetricians, midwives and nurses should be aware that despite sleep-on-side knowledge and high rates of lateral going-to-sleep position, most pregnant women continue to spend a significant amount of time supine during sleep in late pregnancy per our study and previous studies 6–8.…”
Section: Discussionsupporting
confidence: 76%
“…4 This case-control study demonstrated that women who reported settling to sleep in the supine position on the last night of pregnancy were significantly more likely to experience stillbirth, even after accounting for other factors (aOR 2.54 [95% CI 1.04-6.18]). [5][6][7] These studies have also noted differences in maternal sleep duration and number of awakenings between stillbirths and live births. This finding has now been observed in three further studies using similar methodologies with similar effect sizes.…”
Section: Introductionmentioning
confidence: 89%
“…The accompanying editorial and responses to this study highlighted potential confounding factors, including fetal compromise and a small‐for‐gestational‐age fetus, and also raised the possibility of recall bias . Since publication of the Auckland Stillbirth Study, there have been two further studies reporting an association between supine sleep position and late stillbirth that reported aORs of 3.67 and 8.0 . However, these studies were not sufficiently large to test for interactions.…”
Section: Introductionmentioning
confidence: 98%
“…4 A series of case-control studies has been conducted in Australia and New Zealand to investigate modifiable factors associated with late stillbirth (≥ 28 weeks' gestation). [5][6][7] The first of these, the Auckland Stillbirth Study, reported an association between a supine going-to-sleep position and late stillbirth risk [adjusted Odds Ratio (aOR) 2.54, 95% CI 1.04-6.18]. 5 This study also found an association between stillbirth and prolonged sleep duration (>8 hours; aOR 1.71, 95% CI 0.99-2.95) and having a regular daytime sleep (aOR 2.04, 95% CI 1.…”
Section: Introductionmentioning
confidence: 99%